2020
DOI: 10.1111/jcmm.15772
|View full text |Cite
|
Sign up to set email alerts
|

HDAC6‐mediated α‐tubulin deacetylation suppresses autophagy and enhances motility of podocytes in diabetic nephropathy

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…The fusion of autophagosomes with lysosomes was regulated by microtubule stabilization, which was modulated by histone deacetylase 6 (HDAC6)–induced α-tubulin deacetylation ( 29 , 30 ); thus, the structure and acetylation of α-tubulin, as well as HDAC6 activity, were examined to evaluate the stability of microtubules ( 31 , 32 ). The results showed that chondrocytes in the calcified group exhibited disordered and decreased α-tubulin expression ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The fusion of autophagosomes with lysosomes was regulated by microtubule stabilization, which was modulated by histone deacetylase 6 (HDAC6)–induced α-tubulin deacetylation ( 29 , 30 ); thus, the structure and acetylation of α-tubulin, as well as HDAC6 activity, were examined to evaluate the stability of microtubules ( 31 , 32 ). The results showed that chondrocytes in the calcified group exhibited disordered and decreased α-tubulin expression ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The possible underlying mechanism is that acetylation of a-tubulin enhances the endoplasmic reticulum-mitochondria contact, which promotes the formation of autophagosomes (82,83). Additionally, other studies have reported that HDAC6 mediates a-tubulin deacetylation to suppress autophagy in podocytes and human embryonic kidney 293 cells (84,85). However, the underlying mechanisms remain unclear.…”
Section: Hdac6 Deacetylates A-tubulin and Cortactin To Mediate Autophagymentioning
confidence: 99%
“…Bufexamac, an aryl alkanoic acid derivative and a nonsteroidal anti-inflammatory agent for the topical treatment of eczema and other inflammatory skin diseases [ 56 ], is a specific inhibitor of the deacetylases of histone types IIB (HDAC6 and HDAC10 [ 57 ]). Liang et al [ 58 ] proved that HDAC6, a kind of histone deacetylase (HDAC), downregulated the acetylation of α -tubulin, heightened motility, and restrained autophagy in podocytes dealing with AGE, which deteriorated the phenotype of DN, suggesting that HDAC6 is a prospective target for therapy in the early phase of DN. In addition, growing data suggest that the inhibition of HDAC can ameliorate clinical manifestations of diabetic kidney disease and phenotypes such as fibrosis, inflammation, cell death, and albuminuria [ 59 61 ].…”
Section: Discussionmentioning
confidence: 99%